Synthesis of Silver Nanoparticles (NPPs) Using Xylocarpus Granatum Fruit Extract and its Application in Heavy Metal Pollution Detection - Aini, Debi Yulia Ramadhani’; Willian, Nancy; Siregar, Eko Febri Syahputra (PT FORMOSA CENDEKIA GLOBAL, 2024)
Heavy metals are dangerous pollutants because they are toxic, non-biodegradable, and stable. Mercury (Hg) is a type of heavy metal that is often a source of pollution in the aquatic environment. The biosynthesis process of nanoparticles using Xylocarpus granatum fruit extract as a bioreductant has been carried out using the green synthesis method. The research was conducted to synthesize silver nanoparticles (NPP) from Xylocarpus granatum fruit extract to detect heavy metals. The optimum condition of NPP was obtained through the comparison of AgNO3 concentration with extract and reaction time. The optimum NPP produced was at a concentration of AgNO3 1 mM 1:1 at a synthesis time of 2 hours. The NPP formed is selective to Hg metal as can be seen from the color change of NPP from dark brown to clear and sensitive to Hg metal at a concentration of 40 ppm. The calibration curve formed obtained a linear regration value of the relationship between the concentration of Hg standard solution and absorbance, namely y = -0.01330 + 3.71658 with a coefficient of determination (R2) value of 0.99229. Based on the standard curve obtained NPP mangrove fruit extract Xylocarpus granatum has an accuracy of 99.229% in predicting the concentration of the sample.